REPRESENTAÇÕES SOCIAIS SOBRE MÚSICA, ESTILOS MUSICAIS E AULA DE MÚSICA: UMA PROBLEMATIZAÇÃO NECESSÁRIA - Rauski, Rafael Dalalíbera (2015)
As an activity which is present in the human beings everyday life, music is also an element inherent in social inter-relations, and can be taken as the object of different representations. In the current society, music is seen as an activity related to the expression of emotions and feelings, a kind of entertainment or relaxing activity, a means of communication, a way of escaping from or highlighting life problems, an element to be taken advantage of and enjoyed, among others. When specifically approaching music teaching in Brazilian schools, some factors such as the preference for technical and scientific subjects, which have proved economic usefulness, and the conceptions that usually emptied music from its teaching aspect - contributed to the fact that music has not been seen, in several historical periods, as an essential subject in school curricula. The understanding of the reinsertion of music as a compulsory component in Brazilian schools due to the Federal Law nº 11.769/2008, gives rise to an environment of fight for the legitimacy of music as a relevant component in the Brazilian schools, in a context in which the observation of teenagers’ life and practices is of great importance to effect music teaching in the classroom. This also involves considering music resulting from the cultural industry, in a process of construction of meanings that take into consideration the constant changes in the music scenery. In such context, this investigation aims: a) to identify which social representations elementary school 9th grade students hold of music and musical styles; b) to describe how these representations are organized and exposed; c) to analyze the social representations of music lessons held by elementary school 9th grade students. The study was developed in three public schools and in three private schools in the city of Ponta Grossa – PR and region, and was supported by the Social Representations Theory, according to Moscovici and colleagues, and the Social Representations Structural Approach, proposed by Abric in 1976. A qualitative and quantitative approach was employed, with pluri-methodological analysis procedures. The data collection was carried out through questionnaires (N=233), and the data analysis was aided by the software EVOC, COMPLEX, SIMI, ALCESTE and SPSS, in addition to the content analysis. Results revealed that: a) students’ SR are influenced by the family, religion, school musical habits and, mainly by the media. The habit of listening to music is effected through different medias, mainly the mobile ones, and enjoying music is associated to relaxing moments; b) music SR have as their central elements the expression of feelings, well-being and fun, revealing the mediation character ascribed to music by the students; c) musical styles SR present pop, rock and sertanejo (a kind of country music with pop influence in Brazil) as their central nucleus; d) the music lesson is represented by the students as important, but not as much as other subjects. The ideal music lesson SR have fun, favorite musical styles and music practice as central elements; e) The SR investigated are part of an SR system, in which musical styles, fun and relaxation are the most frequent elements; f) The SR investigated suggest some distance between the music lesson which follows the model “conservatory” and the teenagers’ current expectations.